Effect of bio-tissue deformation behavior due to intratumoral injection on magnetic hyperthermia. (1st March 2023) - Tang 汤, Yundong 云东; Zou 邹, Jian 建; Flesch, Rodolfo C.C.; Jin 金, Tao 涛
Abstract : Thermal damage of malignant tissue is generally determined not only by the characteristics of bio-tissues and nanoparticles but also the nanofluid concentration distributions due to different injection methods during magnetic hyperthermia. The latter has more advantages in improving the therapeutic effect with respect to the former since it is a determining factor for the uniformity of nanofluid concentration distribution inside the tumor region. This study investigates the effect of bio-tissue deformation due to intratumoral injection on the thermal damage behavior and treatment temperature distribution during magnetic hyperthermia, in which both the bio-tissue deformation due to nanofluid injection and the mass diffusion after injection behavior are taken into consideration. The nanofluid flow behavior is illustrated by two different theoretical models in this study, which are Navier–Stokes equation inside syringe needle and modified Darcy's law inside bio-tissue. The diffusion behavior after nanofluid injection is expressed by a modified convection–diffusion equation. A proposed three-dimensional liver model based on the angiographic data is set to be the research object in this study, in which all bio-tissues are assumed to be deformable porous media. Simulation results demonstrate that the injection point for syringe needle can generally achieve the maximum value in the tissue pressure, deformation degree, and interstitial flow velocity during the injection process, all of which then drop sharply with the distance away from the injection center. In addition to the bio-tissue deformation due to injection behavior, the treatment temperature is also highly relevant to determine both the diffusion duration and blood perfusion rate due to the thermal damage during the therapy.